Production and characterization of lipases and immobilization of whole cell of the thermophilic Thermomucor indicae seudaticae N31 for transesterification reaction - Ferrarezi, Ana Lucia [UNESP]; Kobe Ohe, Thiago Hideyuki [UNESP]; Borges, Janaina Pires [UNESP]; Brito, Rafaela Rodrigues [UNESP]; Siqueira, Marcos Rechi [UNESP]; Vendramini, Pedro Henrique [UNESP]; Quilles, Jose Carlos [UNESP]; Carreira Nunes, Christiane da Costa [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP]; Boscolo, Mauricio [UNESP]; Da-Silva, Roberto [UNESP]; Gomes, Eleni [UNESP] (Elsevier B.V., 2014)
Among 54 thermophilic fungi tested for lipase production, the highest yield was obtained for Thermomucor indicae seudaticae in submerged (SmF) and solid state fermentation (SSF), being that species selected for studies of fermentative parameters. Some modifications of the culture media afforded an improvement of 15 fold in the lipase activity in SSF and 8 fold in SmF. Furthermore, the lipases produced through both SSF and SmF exhibited maximum lipolytic activity at 40 degrees C but these lipases were different since the enzyme from SmF presented maximum activity at neutral pH (6.0-7.0) whereas the lipase from SSF displayed maximum activity at acidic pH (3.0-4.0). The fungus was grown on loofah sponges, and the immobilized hyphae showed 108 U g - lipolytic activity, a profile including both alkaline and acidic activities. The esterification and transesterification yields were 28% and 13.2% using oleic acid and soybean oil, respectively. Those are essential reactions for biodiesel production. Thus, the lipase production of both the immobilized whole cells as well as the cultivated fungus T. indicae seudaticae N31 may be considered promising in synthesis reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Thermomucor indicae seudaticae; Lipase; Submerged fermentation; Solid state fermentation; Whole cell; Transesterification reaction